Determining the potential of cycling as an urban mode in specific Malaysian contexts / Bayu Martanto Adji - Bayu, Martanto Adji (2015)
The research was designed to invertigate the potential of cycling as transportation mode. There were three studies in this research, namely; first, the potential for cycling as a transportation mode for activities on campus; second, the potential of cycling as feeder mode in public transportation system; and third, the potential of cycling for the trip from home to school. The studies were chosen because the trip in the studies are short distance. The cycling are potential for short distance trips. The first study covers the whole area of the University of Malaya campus in Kuala Lumpur, Malaysia. The second and third study cover one area in Petaling Jaya (PJ), namely Taman Medan area. Sets of questionnaire were designed and distributed and there were two (2) types of survey undertaken for this study i.e. field survey and webbased survey. A total of 1044 respondents were involved in this study. Statistical analysis (Multivariate test) was used to investigate the significant influence of the socioeconomic characteristic on the travel behavior, while the Structural Equation Models (SEM) approach was utilized to rank the impediment factors for cycling. The regression models were develop to investigate the relationship of willingness to cycle againts the travel time and travel cost. The sensitivity analysis also conducted. With regards to the potential for cycling around campus. The potential for cycling is very high. Health and environment concerned are the most considered as the reason for cycling. While the main constraint for cycling is the rainy day. As the result in this study, regarding the cycling facilities, the majority of respondents suggested the exclusive bike path for cycling around campus